Cardiovascular Complications of Novel Anti-Cancer Immunotherapy: Old Problems from New Agents? - Chung, Woo-Baek; Youn, Jong-Chan; Youn, Ho-Joong (Korean circulation journal, 2020)
Many novel anti-cancer therapies have dramatically improved outcomes of various cancer patients. However, it also poses a risk for cardiovascular complications as well. For the novel anti-cancer agent with which physicians does not have enough clinical experiences to determine the characteristics of cardiovascular complications, it is important to assess risk factors for cardiotoxicity before starting anti-cancer therapy. High-risk patient should be consulted to cardiologist before initiating anti-cancer therapy and pre-emptive cardiac function monitoring plan might be prepared in advance. The biomarkers, electrocardiography and echocardiography are useful tools for the detection of subclinical cardiotoxicity during anti-cancer therapy. This review article tried to suggest the cardiac function monitoring strategies for newly encountered potential cardiotoxic anti-cancer agents and to summarize the cardiovascular complications of novel anti-cancer immunotherapies including immune checkpoint inhibitor (ICI) and chimeric antigen receptor (CAR) T-cell therapy. ICIs can cause fatal myocarditis, which usually occurs early after initiation, and prompt treatment with high-dose corticosteroid is necessary. CAR T-cell therapy can cause cytokine release syndrome, which may result in circulatory collapse. Supportive treatment as well as tocilizumab, an anti-interleukin-6 receptor antibody are cornerstones of treatment.